2021
DOI: 10.3389/fcell.2021.769229
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death Protein 1 Blockade Reduces Glycogen Synthase Kinase 3β Activity and Tau Hyperphosphorylation in Alzheimer’s Disease Mouse Models

Abstract: Alzheimer’s disease (AD) is a central nervous system degenerative disease, with no effective treatment to date. Administration of immune checkpoint inhibitors significantly reduces neuronal damage and tau hyperphosphorylation in AD, but the specific mechanism is unclear. Here, we found that programmed cell death-receptor 1 (PD1) and its ligand PDL1 were induced by an intracerebroventricular injection of amyloid-β; they were significantly upregulated in the brains of APP/PS1, 5×FAD mice and in SH-SY5Y-APP cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Using an in vivo study with PD-1 KO mice as a control and immunohistochemical detection, they also found that after Aβ42 insult, the expression of PD-1 and PD-L1 increased. 31 Similar conclusions were drawn from a study by Wu et al in 2022, finding that AD patients exhibit higher levels of PD-L1/2 expression but no difference in PD-1 expression. They utilized flow cytometry on PBMCs extracted from sixteen AD patients.…”
Section: Pd-1/pd-l1 Blockade and Adsupporting
confidence: 81%
“…Using an in vivo study with PD-1 KO mice as a control and immunohistochemical detection, they also found that after Aβ42 insult, the expression of PD-1 and PD-L1 increased. 31 Similar conclusions were drawn from a study by Wu et al in 2022, finding that AD patients exhibit higher levels of PD-L1/2 expression but no difference in PD-1 expression. They utilized flow cytometry on PBMCs extracted from sixteen AD patients.…”
Section: Pd-1/pd-l1 Blockade and Adsupporting
confidence: 81%
“…In the future, developing new senolytic therapies that exclusively target senescent cells, or specifically, senescent microglia should be considered. In line with these contentions are the findings of the beneficial effect of targeting the inhibitory immune checkpoint pathway, PD-1/PD-L1 in animal models of AD and tauopathy, through a mechanism that involves reduced inflammation [43][44][45][46] and anti-aging effect through a mechanism that reduces the abundance of senescent cells in all tissues tested 47,48 .…”
Section: Discussionmentioning
confidence: 78%
“… 170 Recent studies unearthed a PDL1‐GSK3β immune complex within the brains of APP/PS1 and 5×FAD mice, an entity that heightens GSK3β activity and p‐tau levels. 171 …”
Section: The Role Of Gsk3 In Admentioning
confidence: 99%
“…170 Recent studies unearthed a PDL1-GSK3β immune complex within the brains of APP/PS1 and 5×FAD mice, an entity that heightens GSK3β activity and p-tau levels. 171 The preceding paragraph has indicated the potential of ILK to augment the inhibitory effects on GSK3. 7 In N1E-115 neuroblastoma cells, inactivation of ILK led to the loss of its inhibitory effect on GSK3β, which subsequently caused an elevation in p-tau levels.…”
Section: Gsk3 Signaling Mediated By Other Proteins In Tau Pathologymentioning
confidence: 99%